Lower trunk muscle activity during the tennis serve - Chow, J. W.; Shim, J. H.; Lim, Y. T. (Journal of Science and Medicine in Sport, 2003)
Prior electromyographic (EMG) analyses of the tennis serve have focused on the muscles in the hitting arm and shoulder region. This preliminary study aimed to examine the muscle activation patterns of selected lower trunk muscles during three different types of tennis serve--flat, topspin, and slice. Five male highly skilled tennis players completed 10 trials for each type of serve. Surface EMG electrodes were used to monitor the rectus abdominis (RA), external oblique (EO), internal oblique (IO), and lumbar erector spinae (ES) muscles. For each subject, the two trials with the highest self-reported ratings were analysed. Average EMG levels during each phase of a tennis serve for each muscle were analysed using a non-parametric ANOVA design. No major differences in muscle activation pattern were found across different serve types, and bilateral differences in muscle activation were more pronounced in RA and EO than in IO and ES muscles. The abdominal muscles were more active in the topspin than in the other two types of serves during the upward swing of the racket. An appreciable amount of abdominal/low back and bilateral co-activation was observed during certain phases of the serve. The co-activation of lower trunk muscles may help to stabilise the lumbar spine during the arch back and forward swing phases of the serve. The results reinforce the importance of abdominal and low back exercises in the strength and rehabilitation programs designed for tennis players.